AI-driven approaches to reshape forensic practices: automating the tedious, augmenting the astute - Singla, Anu (Cases on forensic and criminological science for criminal detection and avoidance, 2024)
Forensic investigation is ushering into a new era of transformation propelled by rapid technological developments and innovations. The criminals are getting smarter, and crimes are becoming more complex; in such a time dissemination of justice requires commensurate technological enhancement. This chapter explores the vast potential of AI in revolutionizing Forensic Science and provides a succinct overview into the applicability of artificial intelligence (AI) and machine learning (ML) to facilitate classification, characterization, discrimination, differentiation, and recognition of forensic exhibits. This chapter further delves into the fundamental principles of supervised, unsupervised, semi-supervised, and reinforcement learning approaches and describes common ML methods which are frequently employed by researchers of this field.